Numerical Analysis of Carbon Fiber Reinforced Plastic (CFRP) Shear Walls and Steel Strips under Cyclic Loads Using Finite Element Method - Askarizadeh, N.; Mohammadizadeh, M. R. (Engineering, Technology & Applied Science Research, 2017)
Reinforced concrete shear walls are the main elements of resistance against lateral loads in reinforced concrete structures. These walls should not only provide sufficient resistance but also provide sufficient ductility in order to avoid brittle fracture, particularly under strong seismic loads. However, many reinforced concrete shear walls need to be stabilized and reinforced due to various reasons such as changes in requirements of seismic regulations, weaknesses in design and execution, passage of time, damaging environmental factors, patch of rebar in plastic hinges and in some cases failures and weaknesses caused by previous earthquakes or explosion loads. Recently, Fiber Reinforced Polymer (FRP) components have been extensively and successfully used in seismic improvement. This study reinforces FRP reinforced concrete shear walls and steel strips. CFRP and steel strips are evaluated by different yield and ultimate strength. Numerical and experimental studies are done on walls with scale 1/2. These walls are exposed to cyclic loading. Hysteresis curves of force, drift and strain of FRP strips are reviewed in order to compare results of numerical work and laboratory results. Both numerical and laboratory results show that CFRP and steel strips increase resistance, capacity and ductility of the structure.